Our Lost Border : Essays on Life Amid the Narco-violence - Cortez, Sarah; Troncoso, Sergio, 1961- (Arte Público Press, 2013)
This anthology combines writings about the impact of drug violence on life and culture along the U.S.-Mexico border. It reveals how this fragile way of life between two cultures, languages, and countries, has been undermined by the drug trade and the crime that accompanies it, with ramifications far beyond the border region.